SPEED-ACCURACY TRADEOFF IN BASKETBALL SHOOT (Fiep Bulletin - online, 2014)
The aim of the study was to analyze the speed-accuracy relationship in basketball shoot. Fifteen male players (24,47 ± 5,40 years old; experience 11,47 ± 6,10 years) were analyzed performing freethrow shoots. A kinematics analyze (2D, saggital plane, 100 Hz) provided ball's release speed on each shoot. Shoot accuracy was performed through the ball's trajectory analysis. Pearson's correlation test was used to analyze the relationship between speed and shoot accuracy. The relationship between ball's release speed and accuracy test was small (r = 0,22; p>0,05). Therefore, release speed did not seem to be the factor that most determines on shoots accuracy. Players were able to manipulate other variables (such as release angle and height) to compensate release speed. Thus, faster movement may be compensated through greater release angles, this allows a greater area of ball's entry through the basket and decrease the shoot's margin of error. In another way, minor speeds ensure less movement variability.
Keywords: Speed-Accuracy; Basketball Shoot; Basketball